A critical review of the literature to conduct a toxicity assessment for oral exposure to methyl salicylate. (7th February 2017) - Greene, Tracy; Rogers, Sarah; Franzen, Allison; Gentry, Robinan
Abstract: Methyl salicylate is the predominant constituent of oil of wintergreen and is used as a pesticide, a denaturant, an external analgesic, a fragrance ingredient, and a flavoring agent in products such as chewing gum, baked goods, syrups, candy, beverages, ice cream, and tobacco products; and it occurs naturally in some vegetables and berries. Methyl salicylate is of interest to the tobacco industry as oil of wintergreen is used as a flavorant in tobacco products. The purpose of this investigation was to conduct a critical review of the available literature for oral exposure to methyl salicylate, incorporating an analysis of the quality of the studies available and the current understanding of the mode of action. Following a review of all of the available literature, the most appropriate data sets for dose-response modeling were reported by Gulati et al. in which significant changes in reproductive/development endpoints were reported to occur after exposure to 500 mg/kg/d of methyl salicylate in male and female mice. Benchmark dose modeling was performed and the most sensitive endpoint, the number of litters per mating pair, was associated with a BMDL of 220 mg/kg/d. This BMDL was chosen as the point of departure and adjusted by a body weight scaling factor to derive a human equivalent dose. Based on the uncertainty factor analysis, the POD for methyl salicylate was adjusted by a UF of 3 for interspecies uncertainty to derive an allowable daily intake of 11 mg/kg/d.